2012
DOI: 10.1007/s12565-011-0126-6
|View full text |Cite
|
Sign up to set email alerts
|

Absence of musculocutaneous nerve with variations in course and distribution of the median nerve

Abstract: Variations in the brachial plexus and its terminal branches are not uncommon. A communicating branch arising from the musculocutaneous nerve to the median nerve is a frequent variation, but complete merging of musculocutaneous nerve into the median nerve is very rare. Here, we observed variations in the origin, course and distribution of the median nerve in the left upper limb. The musculocutaneous nerve was absent. The median nerve was formed in the upper part of the arm, in front of the brachial artery. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Parchand and Patil reported complete merging of musculocutaneous nerve into median nerve and branches from median nerve innervated the muscles of anterior compartment instead of musculocutaneous nerve as observed in our study. [5][6][7] Malukar and Rathva also reported the absence of musculocutaneous nerve and its fibres pass through the median nerve. 8 Prasad Rao and Chaudhary reported absence of musculocutaneous nerve in 8% of upper limb specimens.…”
Section: Discussionmentioning
confidence: 94%
“…Parchand and Patil reported complete merging of musculocutaneous nerve into median nerve and branches from median nerve innervated the muscles of anterior compartment instead of musculocutaneous nerve as observed in our study. [5][6][7] Malukar and Rathva also reported the absence of musculocutaneous nerve and its fibres pass through the median nerve. 8 Prasad Rao and Chaudhary reported absence of musculocutaneous nerve in 8% of upper limb specimens.…”
Section: Discussionmentioning
confidence: 94%
“…The variations of the median nerve distributions are concerned to have clinical significance to surgeons, radiologists and anatomists in the injured nerve transfer and brachial plexus surgery. The incidences of unusual formation of median nerve have been documented in populations of Americans (Walsh;Uzun & Seelig, 2001), Slovakians (Haviarova et al, 2001), British (Choi et al), Indians (Chauhan & Roy, 2002;Goyal et al, 2005;Anrkooli et al, 2007;Budhiraja et al, 2009;Saralaya et al;Aggarwal et al, 2010;Datta et al, 2011;Sarala et al, 2011;Budhiraja et al, 2011a,b andParchand & Patil, 2013), Saudi Arabians (Saeed & Rufai, 2003), Egyptians (Beheiry, 2004), Iranians (Anrkooli et al), Portuguese (Pais et al, 2010), Kenyas (Ongeti et al, 2012), and Singaporeans (Parchand & Patil), respectively. The present study is the first report demonstrating the incidence of unusual distribution and concomitant formation of the median nerve in Thai's Thai-Northeast cadavers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…dian nerve. Parchand & Patil (2013) reported that there is a complete merging of musculocutaneous nerve into the median nerve, but the coracobrachialis, biceps and brachialis muscles were innervated by the branches of the median nerve. Prasada Rao & Chaudhary (2001) observed absence of musculocutaneous nerve in 8% of 24 upper limbs.…”
Section: Discussionmentioning
confidence: 99%